A method for preparing antistatic wear-resistant polyester fiber fabric

By using modified silver-carrying α-zirconium phosphate and polyester materials for melt spinning in polyester fiber fabrics, the problem of easy accumulation of charge and insufficient wear resistance of polyester fiber fabrics is solved, and the effect of improving antistatic, antibacterial, flame retardant and wear resistance is achieved.

CN119061521BActive Publication Date: 2025-03-18NANTONG SIDEFU TEXTILE DECORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411570539.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-18
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Polyester fiber fabrics have disadvantages such as low moisture rebate, poor breathability of fabrics, and easy accumulation of charge, which limits their application range.

Method used

Modified silver-loaded α-zirconium phosphate was prepared by polymerizing methyl 3-pyrrole formate, pyrrole, and acryloyl pyrrole to the surface of nano-α-zirconium phosphate, and treated with sodium hydroxide solution and loading silver ions in silver nitrate solution. Modified silver-loaded α-zirconium phosphate was prepared by melt-spinning in combination with polyester material to prepare antistatic and wear-resistant polyester fiber fabric.

Benefits of technology

It improves the antistatic, antibacterial, flame retardant and wear resistance of fiber fabrics, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005214563620000121
    Figure GDA0005214563620000121
  • Figure GDA0005214563620000131
    Figure GDA0005214563620000131
Patent Text Reader

Abstract

The invention discloses a method for preparing an antistatic wear-resistant polyester fiber fabric, and relates to the field of fiber fabrics. When preparing the antistatic wear-resistant polyester fiber fabric, the present invention first deposits 3-pyrrole carboxylic acid methyl ester, pyrrole, and acryl pyrrole on the surface of nano α-zirconium phosphate through polymerization, and then treats with sodium hydroxide solution and immerses in a silver nitrate solution to load silver ions to obtain a modified silver-loaded α-zirconium phosphate; terephthalic acid, 5-vinyl isophthalic acid, ethylene glycol, polyethylene glycol, and dodecyl bis-hydroxyethyl methyl ammonium chloride are copolymerized to obtain a polyester material; polyester material and modified silver-loaded α-zirconium phosphate are melt-spun into polyester fibers and woven to obtain antistatic wear-resistant polyester fiber fabric. The antistatic wear-resistant polyester fiber fabric prepared by the present invention has good hygroscopicity, antibacterial properties, and flame retardancy, and has excellent antistatic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fiber fabrics, and in particular to a method for preparing antistatic and wear-resistant polyester fiber fabrics. Background Art

[0002] In recent years, polyester fiber is a synthetic fiber made of organic dibasic acid and diol by chemical polycondensation. It belongs to a kind of polymer compound and is the most important type of synthetic fiber today. Polyester fiber has excellent resistance to organic solvents, soaps, detergents, bleaching liquids, antioxidants, etc. It also has good corrosion resistance and is stable to weak acids and weak bases. Therefore, it has a wide range of uses in the manufacture of home textiles and the manufacture of industrial protective clothing. With the rapid development of the petroleum industry, the raw materials for the production of polyester fibers have become more abundant and cheaper. Coupled with the advancement of chemical, mechanical, electronic automation and other technologies, the production process of polyester fibers has also become more efficient. Therefore, polyester fiber has become the fastest growing and highest-yielding variety among synthetic fibers.

[0003] Polyester fiber has excellent physical, chemical and mechanical properties. Since the industrial production, its textiles have been very popular among consumers. However, polyester fiber has disadvantages such as low moisture regain, poor fabric air permeability, easy accumulation of charge, etc., which affect the expansion of its application range. Based on the above problems, the present invention proposes a preparation method of antistatic wear-resistant polyester fiber fabric, which improves the antibacterial property, flame retardancy and antistatic ability of polyester fiber fabric, and has good market prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an antistatic and wear-resistant polyester fiber fabric to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses an antistatic wear-resistant fiber fabric. The antistatic wear-resistant fiber fabric is prepared by melting and spinning polyester material and modified silver-loaded alpha-zirconium phosphate into polyester fiber and then weaving the polyester fiber.

[0007] As an optimization, the modified silver-loaded α-zirconium phosphate is prepared by first polymerizing 3-pyrrolylcarboxylic acid methyl ester, pyrrole, and acryloyl pyrrole onto the surface of nano α-zirconium phosphate, then treating it with a sodium hydroxide solution and immersing it in a silver nitrate solution to load silver ions.

[0008] As an optimization, the polyester material is obtained by copolymerizing terephthalic acid, 5-vinylisophthalic acid, ethylene glycol, polyethylene glycol, and dodecylbis(hydroxyethyl)methylammonium chloride.

[0009] A method for preparing an antistatic wear-resistant polyester fiber fabric comprises the following preparation steps:

[0010] (1) A pyrrole mixed solution, an α-zirconium phosphate suspension, N-methylformamide, and deionized water are mixed at a mass ratio of 5.5: (8-12): (65-75): (70-80), and stirred at 20-30° C. at a speed of 100-140 r / min for 1-3 h. A 4% ferric chloride solution with a mass concentration of 14-16 times the mass of the α-zirconium phosphate suspension is added at a rate of 5-10 ml / L. The pH value is adjusted to 4-5 with a 1 mol / L nitric acid solution. The mixture is stirred at 0° C. at a speed of 100-140 r / min for 10-14 h. The precipitate is separated by centrifugation, and N-methylformamide is used to separate the precipitate. The modified nano-α-zirconium phosphate is immersed in a sodium hydroxide solution with a mass concentration of 30%, heated at 80-100° C. for 1-2 hours, cooled to room temperature, washed with deionized water for 3-5 times, and immersed in a 0.1 mol / L silver nitrate solution after freeze drying, stirred at 400-600 r / min at 75-85° C. for 5-7 hours, cooled to room temperature, filtered, and the filter residue is washed with deionized water for 3-5 times, and vacuum dried at 60-70° C. for 4-6 hours to obtain the modified silver-loaded α-zirconium phosphate;

[0011] (2) Add terephthalic acid, 5-vinylisophthalic acid and ethylene glycol in a molar ratio of 1:(0.3-0.5):(1.3-1.5) into a reaction kettle, add 0.0003-0.0007 times the mass of terephthalic acid ethylene glycol antimony and 0.0003-0.0007 times the mass of terephthalic acid triphenyl phosphate, introduce nitrogen, esterify at 230-250° C. and 0.2-0.4 MPa, stir at a speed of 70-90 r / min, and set the temperature of the fractionation column at 110-130° C. When the amount of esterification water received is 8 times the theoretical value When the molar amount of ethylene glycol is 6-90%, the pressure is released to normal pressure, and polyethylene glycol with a molar amount of 0.09-0.11 times of terephthalic acid is added, and dodecyl bis(hydroxyethyl)methylammonium chloride with a molar amount of 0.035-0.04 times of terephthalic acid is added, and the reaction is carried out at normal pressure for 1-2 hours. When the amount of esterification water received is 95-97% of the theoretical value, the pressure is reduced to below 50 Pa within 50 minutes and the temperature is raised to 270-280° C., and polycondensation is carried out for 2-3 hours. When the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, stirring is stopped, nitrogen is introduced to restore the pressure to normal pressure, and the polyester material is discharged;

[0012] (3) The polyester material is dried at 105-115° C. for 10-14 h, and the modified silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material are melt-spun at a mass ratio of 1: (0.4-0.6): (30-40), and the fibers are allowed to stand at 130-140° C. for 4-6 h in a nitrogen atmosphere to obtain antistatic and wear-resistant polyester fibers, and the antistatic and wear-resistant fibers are woven to obtain antistatic and wear-resistant polyester fiber fabrics.

[0013] As an optimization, the α-zirconium phosphate suspension in step (1) is prepared by mixing nano α-zirconium phosphate and deionized water in a mass ratio of 1:(8-12) and ultrasonically treating the mixture for 20-30 minutes.

[0014] As an optimization, the pyrrole mixed solution in step (1) is prepared by mixing 3-pyrrole carboxylic acid methyl ester, acryloyl pyrrole, and pyrrole in a mass ratio of 1:1:(3-4):

[0015] As an optimization, the polyethylene glycol in step (2) is polyethylene glycol with a molecular weight of 2000.

[0016] As an optimization, the melt spinning process parameters of step (3) are: spinning temperature of 275-285°C, and spinning rate of 3000m / min.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0018] When preparing the antistatic wear-resistant polyester fiber fabric, the present invention firstly polymerizes and deposits 3-pyrrole carboxylic acid methyl ester, pyrrole and acryl pyrrole on the surface of nano alpha-zirconium phosphate, then treats the nanometer alpha-zirconium phosphate with a sodium hydroxide solution and immerses the nanometer alpha-zirconium phosphate in a silver nitrate solution to load silver ions so as to obtain modified silver-loaded alpha-zirconium phosphate; copolymerizes terephthalic acid, 5-vinyl isophthalic acid, ethylene glycol, polyethylene glycol and dodecyl bis(hydroxyethyl)methylammonium chloride so as to obtain a polyester material; and melt-spins the polyester material and the modified silver-loaded alpha-zirconium phosphate into polyester fibers, which are then woven to obtain the antistatic wear-resistant polyester fiber fabric.

[0019] Firstly, the conductive polymer layer formed by the polymerization and deposition of pyrrole, 3-pyrrolcarboxylic acid methyl ester and acryloylpyrrole on the surface of nano-α-zirconium phosphate can play a good conductive role, which is beneficial to the dissipation of static electricity and improves the antistatic properties of fiber fabrics; the ester group introduced by 3-pyrrolcarboxylic acid methyl ester is hydrolyzed into carboxyl groups, which is beneficial to the adsorption of silver ions, improves the silver-carrying capacity of the modified nano-α-zirconium phosphate, and further improves the antibacterial properties of the fiber fabrics; the nano-α-zirconium phosphate in the modified silver-loaded α-zirconium phosphate can promote carbonization as a phosphorus-containing compound, which is beneficial to the formation of a hard carbon layer in the fiber fabric during combustion, isolates oxygen and heat, and effectively improves the flame retardant properties; and the modified silver-loaded α-zirconium phosphate can be used as a filler in antistatic wear-resistant polyester fibers to improve the wear resistance of antistatic wear-resistant polyester fiber fabrics.

[0020] Secondly, dodecyl bis(hydroxyethyl)methyl ammonium chloride added in the polymerization process of the polyester material introduces a quaternary ammonium salt, which effectively improves the antibacterial properties of the fiber fabric, and the introduction of the quaternary ammonium salt further improves the hydrophilicity of the fiber fabric, which is beneficial to improving the antistatic properties of the fiber fabric; the double bonds contained in the polyester material and the modified silver-loaded α-zirconium phosphate are cross-linked under the action of the initiator during melt extrusion to form a stable network structure, thereby improving the wear resistance of the fiber fabric. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] Embodiment 1, a method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that it comprises the following preparation steps:

[0023] (1) Nano-α-zirconium phosphate and deionized water were mixed at a mass ratio of 1:10 and ultrasonicated for 25 minutes to prepare an α-zirconium phosphate suspension; 3-pyrrolyl carboxylic acid methyl ester, acrylyl pyrrole, pyrrole, α-zirconium phosphate suspension, N-methylformamide, and deionized water were mixed at a mass ratio of 1:1:3:8:65:70, stirred at 20°C at a speed of 100 r / min for 1 hour, a 4% ferric chloride solution with a mass concentration of 14 times the mass of the α-zirconium phosphate suspension was added at a rate of 5 ml / L, the pH was adjusted to 4 with a 1 mol / L nitric acid solution, and the mixture was stirred at 0°C at a speed of 100 r / min for 10 hours, centrifugally separate the precipitate, wash it 3 times with N-methylformamide, wash it 3 times with deionized water, and freeze-dry it to obtain modified nano-α-zirconium phosphate; immerse the modified nano-α-zirconium phosphate in a sodium hydroxide solution with a mass concentration of 30%, heat it at 80°C for 1 hour, cool it to room temperature, wash it 3 times with deionized water, freeze-dry it, immerse it in a 0.1 mol / L silver nitrate solution, stir it at 400 r / min at 75°C for 5 hours, cool it to room temperature, filter it, wash the filter residue with deionized water 3 times, and vacuum dry it at 60°C for 4 hours to obtain modified silver-loaded α-zirconium phosphate;

[0024] (2) Add terephthalic acid, 5-vinylisophthalic acid and ethylene glycol in a molar ratio of 1:0.3:1.3 into a reaction kettle, add 0.0003 times the mass of terephthalic acid ethylene glycol antimony and 0.0003 times the mass of terephthalic acid triphenyl phosphate, introduce nitrogen, esterify at 230°C and 0.2MPa, stir at a speed of 70r / min, and set the temperature of the fractionation column at 110°C. When the amount of esterification water received is 86% of the theoretical value, release the pressure to normal pressure. Add polyethylene glycol in an amount of 0.09 times the molar number of terephthalic acid, add dodecyl bis(hydroxyethyl)methylammonium chloride in an amount of 0.035 times the molar number of terephthalic acid, react for 1 hour at normal pressure, when the amount of esterification water received is 95% of the theoretical value, reduce the pressure to below 50 Pa within 50 minutes and raise the temperature to 270°C, polycondense for 2 hours, stop stirring when the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, introduce nitrogen to restore the pressure to normal pressure, and discharge to obtain a polyester material;

[0025] (3) The polyester material was dried at 105°C for 10 h, and the modified silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material were melt-spun at a mass ratio of 1:0.4:30, the spinning temperature was 275°C, and the spinning rate was 3000 m / min. The antistatic and wear-resistant polyester fiber was allowed to stand at 130°C for 4 h under a nitrogen atmosphere, and the antistatic and wear-resistant fiber was spun to obtain an antistatic and wear-resistant polyester fiber fabric.

[0026] Embodiment 2, a method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that it comprises the following preparation steps:

[0027] (1) Nano-α-zirconium phosphate and deionized water were mixed at a mass ratio of 1:10 and ultrasonicated for 25 minutes to prepare an α-zirconium phosphate suspension; 3-pyrrolyl carboxylic acid methyl ester, acrylyl pyrrole, pyrrole, α-zirconium phosphate suspension, N-methylformamide, and deionized water were mixed at a mass ratio of 1:1:3.5:10:70:75, stirred at 25°C at a speed of 120 r / min for 2 hours, a 4% ferric chloride solution with a mass concentration of 15 times that of the α-zirconium phosphate suspension was added at a rate of 7 ml / L, the pH was adjusted to 4.5 with a 1 mol / L nitric acid solution, and stirred at 0°C at a speed of 1 The mixture was stirred at 20 r / min for 12 h, centrifuged to separate the precipitate, washed with N-methylformamide 4 times, washed with deionized water 4 times, and freeze-dried to obtain modified nano-α-zirconium phosphate; the modified nano-α-zirconium phosphate was immersed in a sodium hydroxide solution with a mass concentration of 30%, heated at 90°C for 1.5 h, cooled to room temperature, washed with deionized water 4 times, and immersed in a 0.1 mol / L silver nitrate solution after freeze-drying, stirred at 500 r / min at 80°C for 6 h, cooled to room temperature, filtered, and the filter residue was washed with deionized water 4 times, and vacuum dried at 65°C for 5 h to obtain modified silver-loaded α-zirconium phosphate;

[0028] (2) Terephthalic acid, 5-vinylisophthalic acid and ethylene glycol were added to a reaction kettle in a molar ratio of 1:0.4:1.4, and 0.0005 times the mass of ethylene glycol antimony and 0.0005 times the mass of terephthalic acid were added to triphenyl phosphate, nitrogen was introduced, and esterification was carried out at 240°C and 0.3MPa. The stirring speed was 80r / min, and the temperature of the fractionation column was 120°C. When the amount of esterification water received was 88% of the theoretical value, the pressure was released to normal pressure, and the reaction mixture was heated to 40 ℃ and 10 ℃. Add polyethylene glycol at a molar amount of 0.1 times that of terephthalic acid, add dodecyl bis(hydroxyethyl)methylammonium chloride at a molar amount of 0.037 times that of terephthalic acid, react for 1.5 hours at normal pressure, when the amount of esterification water received is 96% of the theoretical value, reduce the pressure to below 50 Pa within 50 minutes and raise the temperature to 275°C, polycondense for 2.5 hours, stop stirring when the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, introduce nitrogen to restore the pressure to normal pressure, and discharge to obtain a polyester material;

[0029] (3) The polyester material was dried at 110°C for 12 h, and the modified silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material were melt-spun at a mass ratio of 1:0.5:35, the spinning temperature was 280°C, and the spinning rate was 3000 m / min. The antistatic and wear-resistant polyester fiber was allowed to stand at 135°C for 5 h in a nitrogen atmosphere, and the antistatic and wear-resistant fiber was spun to obtain an antistatic and wear-resistant polyester fiber fabric.

[0030] Embodiment 3, a method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that it comprises the following preparation steps:

[0031] (1) Nano-α-zirconium phosphate and deionized water were mixed at a mass ratio of 1:12 and ultrasonicated for 30 minutes to prepare an α-zirconium phosphate suspension; 3-pyrrolyl carboxylic acid methyl ester, acrylyl pyrrole, pyrrole, α-zirconium phosphate suspension, N-methylformamide, and deionized water were mixed at a mass ratio of 1:1:4:12:75:80, stirred at 30°C and a speed of 140 r / min for 3 hours, a 4% ferric chloride solution with a mass concentration of 16 times the mass of the α-zirconium phosphate suspension was added at a rate of 10 ml / L, the pH was adjusted to 5 with a 1 mol / L nitric acid solution, and the mixture was stirred at 0°C and a speed of 140 r / min for 3 hours. r / min for 14 hours, centrifugally separate the precipitate, wash it with N-methylformamide for 5 times, wash it with deionized water for 5 times, and freeze-dry it to obtain modified nano-α-zirconium phosphate; immerse the modified nano-α-zirconium phosphate in a sodium hydroxide solution with a mass concentration of 30%, heat it at 100°C for 2 hours, cool it to room temperature, wash it with deionized water for 5 times, immerse it in a 0.1 mol / L silver nitrate solution after freeze-drying, stir it at 600 r / min at 85°C for 7 hours, cool it to room temperature, filter it, wash the filter residue with deionized water for 5 times, and vacuum dry it at 70°C for 6 hours to obtain modified silver-loaded α-zirconium phosphate;

[0032] (2) Terephthalic acid, 5-vinylisophthalic acid, and ethylene glycol were added to a reaction kettle in a molar ratio of 1:0.5:1.5, and 0.0007 times the mass of ethylene glycol antimony and 0.0007 times the mass of terephthalic acid were added to triphenyl phosphate, and nitrogen was introduced. Esterification was carried out at 250° C. and 0.4 MPa, and stirring was carried out at a speed of 90 r / min. The temperature of the fractionation column was 130° C. When the amount of esterification water received was 90% of the theoretical value, the pressure was released to normal pressure. , adding polyethylene glycol in an amount of 0.11 times the molar number of terephthalic acid, adding dodecyl bis(hydroxyethyl)methylammonium chloride in an amount of 0.04 times the molar number of terephthalic acid, reacting for 2 hours at normal pressure, when the amount of esterification water received is 97% of the theoretical value, reducing the pressure to below 50 Pa within 50 minutes and raising the temperature to 280°C, polycondensing for 3 hours, stopping stirring when the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, introducing nitrogen to restore the pressure to normal pressure, and discharging to obtain a polyester material;

[0033] (3) The polyester material was dried at 115°C for 14 h, and the modified silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material were melt-spun at a mass ratio of 1:0.6:40, the spinning temperature was 285°C, and the spinning rate was 3000 m / min. The antistatic and wear-resistant polyester fiber was allowed to stand at 140°C for 6 h in a nitrogen atmosphere, and the antistatic and wear-resistant fiber was spun to produce an antistatic and wear-resistant polyester fiber fabric.

[0034] Comparative Example 1, a method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that it comprises the following preparation steps:

[0035] (1) immersing the nano-α-zirconium phosphate in a sodium hydroxide solution with a mass concentration of 30%, heating at 90° C. for 1.5 h, cooling to room temperature, washing with deionized water for 4 times, freeze-drying, immersing in a 0.1 mol / L silver nitrate solution, stirring at 80° C. at 500 r / min for 6 h, cooling to room temperature, filtering, washing the filter residue with deionized water for 4 times, and vacuum drying at 65° C. for 5 h to obtain silver-loaded nano-α-zirconium phosphate;

[0036] (2) Terephthalic acid, 5-vinylisophthalic acid and ethylene glycol were added to a reaction kettle in a molar ratio of 1:0.4:1.4, and 0.0005 times the mass of ethylene glycol antimony and 0.0005 times the mass of terephthalic acid were added to triphenyl phosphate, nitrogen was introduced, and esterification was carried out at 240°C and 0.3MPa. The stirring speed was 80r / min, and the temperature of the fractionation column was 120°C. When the amount of esterification water received was 88% of the theoretical value, the pressure was released to normal pressure, and the reaction mixture was heated to 40 ℃ and 10 ℃. Add polyethylene glycol at a molar amount of 0.1 times that of terephthalic acid, add dodecyl bis(hydroxyethyl)methylammonium chloride at a molar amount of 0.037 times that of terephthalic acid, react for 1.5 hours at normal pressure, when the amount of esterification water received is 96% of the theoretical value, reduce the pressure to below 50 Pa within 50 minutes and raise the temperature to 275°C, polycondense for 2.5 hours, stop stirring when the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, introduce nitrogen to restore the pressure to normal pressure, and discharge to obtain a polyester material;

[0037] (3) The polyester material was dried at 110°C for 12 h, and the silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material were melt-spun at a mass ratio of 1:0.5:35, the spinning temperature was 280°C, and the spinning rate was 3000 m / min. The antistatic wear-resistant polyester fiber was allowed to stand at 135°C for 5 h under a nitrogen atmosphere, and the antistatic wear-resistant fiber was spun to obtain an antistatic wear-resistant polyester fiber fabric.

[0038] Comparative Example 2, a method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that it comprises the following preparation steps:

[0039] (1) Nano-α-zirconium phosphate and deionized water were mixed at a mass ratio of 1:10 and ultrasonicated for 25 minutes to prepare an α-zirconium phosphate suspension; acrylyl pyrrole, pyrrole, α-zirconium phosphate suspension, N-methylformamide, and deionized water were mixed at a mass ratio of 1:4.5:10:70:75, stirred at 25°C at a speed of 120 r / min for 2 hours, 15 times the mass of the α-zirconium phosphate suspension The mass concentration of 4% ferric chloride solution was added at a rate of 7 ml / L, the pH was adjusted to 4.5 with a 1 mol / L nitric acid solution, and the mixture was stirred at 0°C at a speed of 120 r / min n stirring for 12 hours, centrifuging and separating the precipitate, washing with N-methylformamide 4 times, washing with deionized water 4 times, and freeze-drying to obtain modified nano-α-zirconium phosphate; immersing the modified nano-α-zirconium phosphate in a sodium hydroxide solution with a mass concentration of 30%, heating at 90°C for 1.5 hours, cooling to room temperature, washing with deionized water 4 times, and then freeze-drying and immersing in a 0.1 mol / L silver nitrate solution, stirring at 80°C and 500 r / min for 6 hours, cooling to room temperature, filtering, washing the filter residue with deionized water 4 times, and vacuum drying at 65°C for 5 hours to obtain modified silver-loaded α-zirconium phosphate;

[0040] (2) Terephthalic acid, 5-vinylisophthalic acid and ethylene glycol were added to a reaction kettle in a molar ratio of 1:0.4:1.4, and 0.0005 times the mass of ethylene glycol antimony and 0.0005 times the mass of terephthalic acid were added to triphenyl phosphate, nitrogen was introduced, and esterification was carried out at 240°C and 0.3MPa. The stirring speed was 80r / min, and the temperature of the fractionation column was 120°C. When the amount of esterification water received was 88% of the theoretical value, the pressure was released to normal pressure, and the reaction mixture was heated to 40 ℃ and 10 ℃. Add polyethylene glycol at a molar amount of 0.1 times that of terephthalic acid, add dodecyl bis(hydroxyethyl)methylammonium chloride at a molar amount of 0.037 times that of terephthalic acid, react for 1.5 hours at normal pressure, when the amount of esterification water received is 96% of the theoretical value, reduce the pressure to below 50 Pa within 50 minutes and raise the temperature to 275°C, polycondense for 2.5 hours, stop stirring when the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, introduce nitrogen to restore the pressure to normal pressure, and discharge to obtain a polyester material;

[0041] (3) The polyester material was dried at 110°C for 12 h, and the modified silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material were melt-spun at a mass ratio of 1:0.5:35, the spinning temperature was 280°C, and the spinning rate was 3000 m / min. The antistatic and wear-resistant polyester fiber was allowed to stand at 135°C for 5 h in a nitrogen atmosphere, and the antistatic and wear-resistant fiber was spun to obtain an antistatic and wear-resistant polyester fiber fabric.

[0042] Comparative Example 3, a method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that it comprises the following preparation steps:

[0043] (1) Terephthalic acid, 5-vinylisophthalic acid and ethylene glycol were added to a reaction kettle in a molar ratio of 1:0.4:1.4, and 0.0005 times the mass of ethylene glycol antimony and 0.0005 times the mass of terephthalic acid were added to triphenyl phosphate, nitrogen was introduced, esterification was carried out at 240°C and 0.3MPa, stirring was carried out at a speed of 80r / min, the temperature of the fractionation column was 120°C, and the pressure was released to normal pressure when the amount of esterification water received was 88% of the theoretical value, and the reaction mixture was heated to 40 ℃ and 10 ℃. Add polyethylene glycol at a molar amount of 0.1 times that of terephthalic acid, add dodecyl bis(hydroxyethyl)methylammonium chloride at a molar amount of 0.037 times that of terephthalic acid, react for 1.5 hours at normal pressure, when the amount of esterification water received is 96% of the theoretical value, reduce the pressure to below 50 Pa within 50 minutes and raise the temperature to 275°C, polycondense for 2.5 hours, stop stirring when the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, introduce nitrogen to restore the pressure to normal pressure, and discharge to obtain a polyester material;

[0044] (2) The polyester material was dried at 110°C for 12 hours and then melt-spun at a spinning temperature of 280°C and a spinning rate of 3000 m / min. The antistatic and wear-resistant polyester fiber was allowed to stand at 135°C for 5 hours under a nitrogen atmosphere to obtain the antistatic and wear-resistant polyester fiber. The antistatic and wear-resistant fiber was spun to obtain the antistatic and wear-resistant polyester fiber fabric.

[0045] Comparative Example 4, a method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that it comprises the following preparation steps:

[0046] (1) Nano-α-zirconium phosphate and deionized water were mixed at a mass ratio of 1:10 and ultrasonicated for 25 minutes to prepare an α-zirconium phosphate suspension; 3-pyrrolyl carboxylic acid methyl ester, acrylyl pyrrole, pyrrole, α-zirconium phosphate suspension, N-methylformamide, and deionized water were mixed at a mass ratio of 1:1:3.5:10:70:75, stirred at 25°C at a speed of 120 r / min for 2 hours, a 4% ferric chloride solution with a mass concentration of 14 to 16 times the mass of the α-zirconium phosphate suspension was added at a rate of 7 ml / L, the pH was adjusted to 4.5 with a 1 mol / L nitric acid solution, and the mixture was stirred at 0°C at a speed of 120 r / min. The mixture was stirred at 120 r / min for 12 h, centrifuged to separate the precipitate, washed with N-methylformamide 4 times, washed with deionized water 4 times, and freeze-dried to obtain modified nano-α-zirconium phosphate; the modified nano-α-zirconium phosphate was immersed in a sodium hydroxide solution with a mass concentration of 30%, heated at 90°C for 1.5 h, cooled to room temperature, washed with deionized water 4 times, and immersed in a 0.1 mol / L silver nitrate solution after freeze-drying, stirred at 500 r / min at 80°C for 6 h, cooled to room temperature, filtered, and the filter residue was washed with deionized water 4 times, and vacuum dried at 65°C for 5 h to obtain modified silver-loaded α-zirconium phosphate;

[0047] (2) Add terephthalic acid, 5-vinylisophthalic acid and ethylene glycol in a molar ratio of 1:0.4:1.4 to a reactor, add 0.0005 times the mass of terephthalic acid ethylene glycol antimony and 0.0005 times the mass of terephthalic acid triphenyl phosphate, introduce nitrogen, esterify at 240°C and 0.3MPa, stir at a speed of 80r / min, and set the temperature of the fractionation column to 120°C. When the amount of esterification water received is 88% of the theoretical value, release the pressure to normal pressure, add 0.1 times the molar number of terephthalic acid polyethylene glycol, react at normal pressure for 1.5h, and when the amount of esterification water received is 96% of the theoretical value, reduce the pressure to below 50Pa within 50min and raise the temperature to 275°C for condensation for 2.5h. When the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, stop stirring, introduce nitrogen to restore the pressure to normal pressure, and discharge the material to obtain a polyester material;

[0048] (3) The polyester material was dried at 110°C for 12 h, and the modified silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material were melt-spun at a mass ratio of 1:0.5:35, the spinning temperature was 280°C, and the spinning rate was 3000 m / min. The antistatic and wear-resistant polyester fiber was allowed to stand at 135°C for 5 h in a nitrogen atmosphere, and the antistatic and wear-resistant fiber was spun to obtain an antistatic and wear-resistant polyester fiber fabric.

[0049] Comparative Example 5, a method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that it comprises the following preparation steps:

[0050] (1) Nano-α-zirconium phosphate and deionized water were mixed at a mass ratio of 1:10 and ultrasonicated for 25 minutes to prepare an α-zirconium phosphate suspension; 3-pyrrolyl carboxylic acid methyl ester, pyrrole, α-zirconium phosphate suspension, N-methylformamide, and deionized water were mixed at a mass ratio of 1:3.5:10:70:75, stirred at 25°C at a speed of 120 r / min for 2 hours, a 4% ferric chloride solution with a mass concentration of 150 times the mass of 3-pyrrolyl carboxylic acid methyl ester was added at a rate of 7 ml / L, the pH was adjusted to 4.5 with a 1 mol / L nitric acid solution, and the mixture was stirred at 0°C at a speed of 120 r / m in stirring for 12 hours, centrifugally separating the precipitate, washing with N-methylformamide 4 times, washing with deionized water 4 times, and freeze-drying to obtain modified nano-α-zirconium phosphate; immersing the modified nano-α-zirconium phosphate in a sodium hydroxide solution with a mass concentration of 30%, heating at 90°C for 1.5 hours, cooling to room temperature, washing with deionized water 4 times, and then freeze-drying and immersing in a 0.1 mol / L silver nitrate solution, stirring at 80°C and 500 r / min for 6 hours, cooling to room temperature, filtering, washing the filter residue with deionized water 4 times, and vacuum drying at 65°C for 5 hours to obtain modified silver-loaded α-zirconium phosphate;

[0051] (2) Terephthalic acid and ethylene glycol were added to a reactor in a molar ratio of 1:1, and 0.0005 times the mass of terephthalic acid ethylene glycol antimony and 0.0005 times the mass of terephthalic acid triphenyl phosphate were added, nitrogen was introduced, esterification was carried out at 240°C and 0.3MPa, stirring was carried out at a speed of 80r / min, the temperature of the fractionation column was 120°C, and the pressure was released to normal pressure when the amount of esterification water received was 88% of the theoretical value, and terephthalic acid was added. 0.1 times of polyethylene glycol, add 0.037 times of terephthalic acid molar number of dodecyl bis (hydroxyethyl) methyl ammonium chloride, react for 1.5 hours at normal pressure, when the esterification water receiving amount is 96% of the theoretical value, reduce the pressure to below 50Pa within 50 minutes and raise the temperature to 275°C, polycondense for 2.5 hours, stop stirring when the ethylene glycol distillation amount is greater than 92% of the theoretical value, introduce nitrogen to restore the pressure to normal pressure, and discharge to obtain polyester material;

[0052] (3) The polyester material was dried at 110°C for 12 h, and the modified silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material were melt-spun at a mass ratio of 1:0.5:35, the spinning temperature was 280°C, and the spinning rate was 3000 m / min. The antistatic and wear-resistant polyester fiber was allowed to stand at 135°C for 5 h in a nitrogen atmosphere, and the antistatic and wear-resistant fiber was spun to obtain an antistatic and wear-resistant polyester fiber fabric.

[0053] Test Example 1, test of antistatic performance:

[0054] (1) Moisture regain test: 3 portions of antistatic wear-resistant polyester fibers dried to constant weight were placed in a constant temperature and humidity chamber at 20°C and 65% for 48 hours and then taken out. The moisture regain was calculated based on the mass difference before and after being placed in the constant temperature and humidity chamber. The results are shown in Table 1.

[0055] (2) Volume resistivity test: The volume resistivity of antistatic wear-resistant polyester fiber was tested using a YG321 fiber resistivity meter produced by Nantong Sansi Electromechanical Technology Co., Ltd. The test was conducted in accordance with GB / T14342-93 "Test method for resistivity of synthetic staple fibers". The results are shown in Table 1.

[0056] Table 1

[0057] Moisture regain Volume specific resistance Moisture regain Volume specific resistance Example 1 3.26% <![CDATA[0.79×10 6 Ohm cm]]> Comparative Example 1 3.16% <![CDATA[6.94×10 7 Ohm cm]]> Example 2 3.42% <![CDATA[9.61×10 5 Ohm cm]]> Comparative Example 2 3.26% <![CDATA[1.01×10 7 Ohm cm]]> Example 3 3.31% <![CDATA[1.03×10 6 Ohm cm]]> Comparative Example 3 2.97% <![CDATA[4.55×10 7 Ohm cm]]> Comparative Example 4 2.68% <![CDATA[5.27×10 6 Ohm cm]]> Comparative Example 5 3.27% <![CDATA[3.44×10 6 Ohm cm]]>

[0058] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the antistatic and wear-resistant polyester fiber fabric prepared in the present invention has good antistatic performance.

[0059] The moisture regain of Examples 1 to 3 is greater than that of Comparative Example 4, indicating that the dodecyl bis(hydroxyethyl)methylammonium chloride introduced during the polymerization of the polyester composite material improves the hydrophilicity of the polyester composite material, and the improvement in hydrophilicity further improves the antistatic properties of the fiber fabric; the volume resistivity of Examples 1 to 3 is less than that of Comparative Examples 1 and 3, indicating that the conductive polymer layer formed by the deposition polymerization of pyrrole, 3-pyrrolcarboxylic acid methyl ester, and acrylpyrrole on the surface of nano-α-zirconium phosphate can play a good conductive role, which is beneficial to the dissipation of static electricity and improves the antistatic properties of the fiber fabric.

[0060] Test Example 2, flame retardant performance test:

[0061] Test method: According to GB / T2406-93, the limiting oxygen index of the embodiment and the comparative example was tested using an oxygen index instrument. The results are shown in Table 2.

[0062] Table 2

[0063] Limiting oxygen index Limiting oxygen index Example 1 36.2% Comparative Example 1 36.4% Example 2 37.1% Comparative Example 2 36.9% Example 3 36.7% Comparative Example 3 28.3% Comparative Example 4 36.1% Comparative Example 5 36.3%

[0064] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the antistatic and wear-resistant polyester fiber fabric prepared in the present invention has good flame retardant properties.

[0065] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the limiting oxygen index of Examples 1 to 3 is significantly improved compared with that of Comparative Example 3, indicating that the nano-α-zirconium phosphate in the modified silver-loaded α-zirconium phosphate as a phosphorus-containing compound can promote carbonization, which is beneficial to the formation of a hard carbon layer in the fiber fabric during the combustion process, isolating oxygen and heat, and effectively improving the flame retardant performance.

[0066] Test Example 3, Antibacterial Performance: The fiber fabrics obtained in each embodiment and comparative example were crushed into powders of less than 150 microns, and the same mass was taken to test the antibacterial rate of the materials against Staphylococcus aureus according to the Quine test method. The results are shown in Table 3.

[0067] Table 3

[0068]

[0069]

[0070] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the antistatic and wear-resistant polyester fiber fabric prepared by the present invention has good antibacterial properties.

[0071] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the antibacterial rate of Examples 1 to 3 is significantly improved compared with that of Comparative Examples 1 and 3, indicating that the silver ions on the modified silver-loaded α-zirconium phosphate can effectively exert antibacterial properties; the antibacterial rate of Examples 1 to 3 is significantly improved compared with that of Comparative Example 2, indicating that the carboxyl group formed after the hydrolysis of 3-pyrrolylcarboxylic acid methyl ester improves the adsorption of silver ions by nano-α-zirconium phosphate and improves the antibacterial properties of the antistatic and wear-resistant polyester fiber fabric; the antibacterial rate of Examples 1 to 3 is significantly improved compared with that of Comparative Example 4, indicating that the cationic quaternary ammonium salt in the polyester material effectively improves the antibacterial properties of the antistatic and wear-resistant polyester fiber fabric.

[0072] Test Example 4, abrasion resistance: The abrasion resistance was tested using Nu-Martindale 864 abrasion tester according to GB / T21196.3-2007. The fabric to be tested was cut into a circle with a diameter of 38±0.5 mm, and a standard 600-mesh water sandpaper was used as an abrasive (the abrasive was replaced once the number of times exceeded 5000), the pressure was 9 kPa, and the breakage of two independent yarns of the fabric was taken as the end point of abrasion resistance, and the number of abrasion resistance times was recorded. The results are shown in Table 4.

[0073] Table 4

[0074] Wear times Wear times Example 1 2591 Comparative Example 1 1677 Example 2 2847 Comparative Example 2 2692 Example 3 2796 Comparative Example 3 1011 Comparative Example 4 2784 Comparative Example 5 1529

[0075] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the antistatic wear-resistant polyester fiber fabric prepared by the present invention has good wear resistance.

[0076] From the comparison of the experimental data of Examples 1 to 3 and Comparative Example 3 in Table 4, it can be found that the wear times of Examples 1 to 3 are significantly improved compared with that of Comparative Example 3, indicating that the modified silver-loaded α-zirconium phosphate acting as a filler can improve the wear resistance of the antistatic wear-resistant polyester fiber fabric; the wear times of Examples 1 to 3 are significantly improved compared with Comparative Examples 1 and 5, indicating that the double bonds in the modified silver-loaded α-zirconium phosphate and the polyester material form a cross-linked network under the action of the initiator, which effectively improves the wear resistance of the antistatic wear-resistant polyester fiber fabric.

[0077] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An antistatic wear-resistant polyester fiber fabric, characterized in that: The antistatic wear-resistant fiber fabric is prepared by melting and spinning polyester material and modified silver-loaded α-zirconium phosphate into polyester fiber and then weaving the polyester fiber; The polyester material is prepared by copolymerizing terephthalic acid, 5-vinylisophthalic acid, ethylene glycol, polyethylene glycol, and dodecylbishydroxyethylmethylammonium chloride; The modified silver-loaded alpha-zirconium phosphate is prepared by first polymerizing 3-pyrrolyl carboxylic acid methyl ester, pyrrole, and acryloyl pyrrole and depositing them on the surface of nano-alpha-zirconium phosphate, then treating them with a sodium hydroxide solution and immersing them in a silver nitrate solution to load silver ions.

2. A method for preparing an antistatic wear-resistant polyester fiber fabric, characterized in that: The method comprises the following preparation steps: (1) 3-pyrrolyl carboxylic acid methyl ester, acryloyl pyrrole and pyrrole are mixed in a mass ratio of 1:1:(3-4) to prepare a pyrrole mixed solution; the pyrrole mixed solution, α-zirconium phosphate suspension, N-methylformamide and deionized water are mixed in a mass ratio of 5.5:(8-12):(65-75):(70-80), and stirred at a speed of 100-140 r / min at 20-30°C for 1-3 h; a 4% ferric chloride solution with a mass concentration of 14-16 times the mass of the α-zirconium phosphate suspension is added at a rate of 5-10 ml / L; the pH is adjusted to 4-5 with a 1 mol / L nitric acid solution; and the mixture is stirred at a speed of 100-140 r / min at 0°C. n stirring for 10-14 hours, centrifugally separating the precipitate, washing with N-methylformamide for 3-5 times, washing with deionized water for 3-5 times, and freeze-drying to obtain modified nano-α-zirconium phosphate; immersing the modified nano-α-zirconium phosphate in a sodium hydroxide solution with a mass concentration of 30%, heating at 80-100°C for 1-2 hours, cooling to room temperature, washing with deionized water for 3-5 times, freeze-drying and immersing in a 0.1 mol / L silver nitrate solution, stirring at 400-600 r / min at 75-85°C for 5-7 hours, cooling to room temperature, filtering, washing the filter residue with deionized water for 3-5 times, and vacuum drying at 60-70°C for 4-6 hours to obtain modified silver-loaded α-zirconium phosphate; (2) Add terephthalic acid, 5-vinylisophthalic acid and ethylene glycol in a molar ratio of 1: (0.3-0.5): (1.3-1.5) into a reactor, add 0.0003-0.0007 times the mass of terephthalic acid ethylene glycol antimony and 0.0003-0.0007 times the mass of terephthalic acid triphenyl phosphate, introduce nitrogen, esterify at 230-250°C and 0.2-0.4MPa, stir at a speed of 70-90r / min, and set the temperature of the fractionation column at 110-130°C. When the amount of esterification water received is 8 times the theoretical value, When the molar amount of ethylene glycol is 6-90%, the pressure is released to normal pressure, and polyethylene glycol with a molar amount of 0.09-0.11 times of terephthalic acid is added, and dodecyl bis(hydroxyethyl)methylammonium chloride with a molar amount of 0.035-0.04 times of terephthalic acid is added. The reaction is carried out at normal pressure for 1-2 hours. When the amount of esterification water received is 95-97% of the theoretical value, the pressure is reduced to below 50 Pa within 50 minutes and the temperature is raised to 270-280°C. The polycondensation is carried out for 2-3 hours. When the amount of ethylene glycol evaporated is greater than 92% of the theoretical value, the stirring is stopped, nitrogen is introduced to restore the pressure to normal pressure, and the polyester material is discharged; (3) The polyester material is dried at 105-115°C for 10-14 h, and the modified silver-loaded α-zirconium phosphate, diisopropylbenzene peroxide, and polyester material are melt-spun in a mass ratio of 1: (0.4-0.6): (30-40), and the fibers are allowed to stand at 130-140°C for 4-6 h in a nitrogen atmosphere to obtain antistatic and wear-resistant polyester fibers, and the antistatic and wear-resistant fibers are spun to obtain antistatic and wear-resistant polyester fiber fabrics.

3. The method for preparing an antistatic wear-resistant polyester fiber fabric according to claim 2, characterized in that: The α-zirconium phosphate suspension in step (1) is prepared by mixing nano α-zirconium phosphate and deionized water in a mass ratio of 1:(8-12) and ultrasonically treating the mixture for 20-30 minutes.

4. The method for preparing an antistatic wear-resistant polyester fiber fabric according to claim 2, characterized in that: The polyethylene glycol in step (2) is polyethylene glycol with a molecular weight of 2000.

5. The method for preparing an antistatic wear-resistant polyester fiber fabric according to claim 2, characterized in that: The melt spinning process parameters in step (3) are: spinning temperature of 275-285°C and spinning rate of 3000 m / min.

Citation Information

Patent Citations

  • Antibacterial polyester fiber based on silver-loaded zirconium phosphate and preparation method thereof

    CN105332078A

  • Nano-silver loaded mesoporous zirconium phosphate antibacterial polyester fiber and preparation method thereof

    CN105332087A